Predictors of Inappropriate Use of Diagnostic Tests and Management of Bronchiolitis - Rojas-Soto, G (Hindawi Limited, 2017)
Background. The aim of the present study was to determine predictors of inappropriate use of diagnostic tests and management of bronchiolitis in a population of hospitalized infants. Methods. In an analytical cross-sectional study, we determined independent predictors of the inappropriate use of diagnostic tests and management of bronchiolitis in a population of hospitalized infants. We defined a composite outcome score as the main outcome variable. Results. Of the 303 included patients, 216 (71.3%) experienced an inappropriate use of diagnostic tests and treatment of bronchiolitis. After controlling for potential confounders, it was found that atopic dermatitis (OR 5.30; CI 95% 1.14-24.79; p=0.034), length of hospital stay (OR 1.48; CI 95% 1.08-2.03; p=0.015), and the number of siblings (OR 1.92; CI 95% 1.13-3.26; p=0.015) were independent predictors of an inappropriate use of diagnostic tests and treatment of the disease. Conclusions. Inappropriate use of diagnostic tests and treatment of bronchiolitis was a highly prevalent outcome in our population of study. Participants with atopic dermatitis, a longer hospital stay, and a greater number of siblings were at increased risk for inappropriate use of diagnostic tests and management of the disease. © 2017 Lorena Sarmiento et al.